2022
DOI: 10.26636/jtit.2022.155921
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Various Edge Detection Techniques for Underwater Images

Abstract: Nowadays, underwater image identification is a challenging task for many researchers focusing on various applications, such as tracking fish species, monitoring coral reef species, and counting marine species. Because underwater images frequently suffer from distortion and light attenuation, pre-processing steps are required in order to enhance their quality. In this paper, we used multiple edge detection techniques to determine the edges of the underwater images. The pictures were pre-processed with the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Then it can be concluded that Canny's algorithm has the best performance with entropy and PSNR on Tisha images 1.5701 and 10.9043 and Diya images 1.5477 and 9.6982. [26] study used the Sobel, Prewitt, Roberts, Laplacian, and Canny algorithms to detect Acropora branches underwater. In this study, 100 Acropora branching image data were used.…”
Section: Related Workmentioning
confidence: 99%
“…Then it can be concluded that Canny's algorithm has the best performance with entropy and PSNR on Tisha images 1.5701 and 10.9043 and Diya images 1.5477 and 9.6982. [26] study used the Sobel, Prewitt, Roberts, Laplacian, and Canny algorithms to detect Acropora branches underwater. In this study, 100 Acropora branching image data were used.…”
Section: Related Workmentioning
confidence: 99%